Deletion of Nuclear Factor kappa B p50 Subunit Decreases Inflammatory Response and Mildly Protects Neurons from Transient Forebrain Ischemia-induced Damage - Rolova, Taisia (Aging Dis, 2015)
Transient forebrain ischemia induces delayed death of the hippocampal pyramidal neurons, particularly in the CA2 and medial CA1 area. Early pharmacological inhibition of inflammatory response can ameliorate neuronal death, but it also inhibits processes leading to tissue regeneration. Therefore, research efforts are now directed to modulation of post-ischemic inflammation, with the aim to promote beneficial effects of inflammation and limit adverse effects. Transcription factor NF-κB plays a key role in the inflammation and cell survival/apoptosis pathways. In the brain, NF-κB is predominantly found in the form of a heterodimer of p65 (RelA) and p50 subunit, where p65 has a transactivation domain while p50 is chiefly involved in DNA binding. In this study, we subjected middle-aged Nfkb1 knockout mice (lacking p50 subunit) and wild-type controls of both sexs to 17 min of transient forebrain ischemia and assessed mouse performance in a panel of behavioral tests after two weeks of post-operative recovery. We found that ischemia failed to induce clear memory and motor deficits, but affected spontaneous locomotion in genotype- and sex-specific way. We also show that both the lack of the NF-κB p50 subunit and female sex independently protected CA2 hippocampal neurons from ischemia-induced cell death. Additionally, the NF-κB p50 subunit deficiency significantly reduced ischemia-induced microgliosis, astrogliosis, and neurogenesis. Lower levels of hippocampal microgliosis significantly correlated with faster spatial learning. We conclude that NF-κB regulates the outcome of transient forebrain ischemia in middle-aged subjects in a sex-specific way, having an impact not only on neuronal death but also specific inflammatory responses and neurogenesis.